Effect of Photodynamic Therapy on Gemcitabine-Resistant Cholangiocarcinoma in vitro and in vivo Through KLF10 and EGFR - Yang, Yang; Li, Jigang; Yao, Lei; Wu, Lile (Frontiers in Cell and Developmental Biology, 2021)
Cholangiocarcinoma is a relatively rare neoplasm with increasing incidence. Although chemotherapeutic agent such as gemcitabine has long been used as standard treatment for cholangiocarcinoma, the interindividual variability in target and drug sensitivity and specificity may lead to therapeutic resistance. In the present study, we found that photodynamic therapy (PDT) treatment inhibited gemcitabine-resistant cholangiocarcinoma cells via repressing cell viability, enhancing cell apoptosis, and eliciting G1 cell cycle arrest through modulating Cyclin D1 and caspase 3 cleavage. In vivo, PDT treatment significantly inhibited the growth of gemcitabine-resistant cholangiocarcinoma cell-derived tumors. Online data mining and experimental analyses indicate that KLF10 expression was induced, whereas EGFR expression was downregulated by PDT treatment; KLF10 targeted the EGFR promoter region to inhibit EGFR transcription. Under PDT treatment, EGFR overexpression and KLF10 silencing attenuated the anti-cancer effects of PDT on gemcitabine-resistant cholangiocarcinoma cells by promoting cell viability, inhibiting apoptosis, and increasing S phase cell proportion. Importantly, under PDT treatment, the effects of KLF10 silencing were significantly reversed by EGFR silencing. In conclusion, PDT treatment induces KLF10 expression and downregulates EGFR expression. KLF10 binds to EGFR promoter region to inhibit EGFR transcription. The KLF10/EGFR axis participates in the process of the inhibition of PDT on gemcitabine-resistant cholangiocarcinoma cells.